Late‐News Poster: Design for a Flexible Autostereoscopic Display with Different Radius of Curvature. Issue 1 (June 2014) - Cheng, Yun‐Ting; Huang, Kuo‐Chung; Lin, Hoang Yan; Hsu, Wan‐Hsuan; Hsiao, Li‐Jen
Abstract Radius of curvature is an important factor for flexible displays, especially in 3D field; however little research has been done. This paper provides a design reference for flexible autostereoscopic (AS3D) displays with different radius of curvature based on a ray‐tracing approach. The recommended design radius of curvature for 4‐inch‐wide (10‐cm) two‐view flexible AS3D is the value larger than 30 cm.